2020
DOI: 10.5005/jp-journals-10006-1827
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes among Women with Cholestasis of Pregnancy

Abstract: Introduction: Intrahepatic cholestasis of pregnancy (ICP), also described as obstetric cholestasis is the second most common cause of icterus in pregnancy. Although not fully understood, proposed theories indicate it could be due to decreased bile flow through the liver and its poor excretion, leading to increased levels of colic and chenodeoxycholic acid. It is known to be associated with adverse maternal and fetal outcomes. Materials and methods: The data were collected by retrospective record review for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Hapangama and Neilson 3 did a Cochrane review including 1,108 women of 10 trials and found that mifepristone-treated women were more likely to be in labor or to have favorable cervix at 48 hours (RR 2.41, 95% confidence interval 1.7-3.42); these women had less chances to have LSCS (RR 0.74, 95% confidence interval 0.6-0.92). Minimum effective dose of mifepristone was 200 mg. Vijay et al 13 studied perinatal outcome in patients with cholestasis and found that pregnancies induced with PGE2 (dinoprostone) and PGE1 (misoprostol) had 54.7% chance of undergoing lower segment cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Hapangama and Neilson 3 did a Cochrane review including 1,108 women of 10 trials and found that mifepristone-treated women were more likely to be in labor or to have favorable cervix at 48 hours (RR 2.41, 95% confidence interval 1.7-3.42); these women had less chances to have LSCS (RR 0.74, 95% confidence interval 0.6-0.92). Minimum effective dose of mifepristone was 200 mg. Vijay et al 13 studied perinatal outcome in patients with cholestasis and found that pregnancies induced with PGE2 (dinoprostone) and PGE1 (misoprostol) had 54.7% chance of undergoing lower segment cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal is to refine prenatal care protocols, thereby contributing to the improved health and well-being of both the mother and the developing fetus. This research not only underscores the importance of maintaining optimal AFI levels but also provides invaluable insights into clinical practice, paving the way for advancements in antenatal care techniques and pregnancy outcomes (5). Through this comprehensive approach, the study bridges existing knowledge gaps and furthers our understanding of the critical role played by AFI in fetal development.…”
Section: Introductionmentioning
confidence: 81%
“…2 Although maternal invariably increased fetal risk , namely preterm delivery, low birth weight babies, bradycardia, meconium staining of amniotic fluid, fetal distress, intrauterine death of fetus. 3 Both spontaneous and iatrogenic MSL, RDS, increased neonatal ICU admission. 4…”
mentioning
confidence: 99%